Diversification and Development as a Tool for Structural Transformation in the Kingdom of Saudi Arabia - Sallam, Mohamed A. M.; Zaki, Amal Essam; Abdelsamiea, Abdelsamiea Tahsin (Journal of Posthumanism, 2025)
This paper examines how economic diversification drives structural transformation in Saudi Arabia, tackling the challenges of oil dependency that threaten long-term economic stability. Based on annual data from 1991 to 2022, the analysis employs the Structural Transformation Index, incorporating key variables such as diversification, economic complexity, investment, GDP growth, and oil prices. The asymmetric relationship brought about by oil price increases is larger compared to the drops, according to the Nonlinear ARDL methodology. These results indicate a stable long-run relationship, where diversification, investment, and growth positively contribute to transformation, while economic complexity exhibits paradoxical negative long-term effects. The study suggests the following: the intensification of successful diversification policy, strategic investment of oil revenues, encouragement of economic complexity, creation of conducive investment environments, and nonlinear policy frameworks that account for these asymmetric dynamics.